2012
DOI: 10.1016/j.bpj.2011.11.1617
|View full text |Cite
|
Sign up to set email alerts
|

From Thermodynamic States to Biological Function by Einstein's Approach to Statistical Physics

Abstract: Tethers are thin tubes of lipids (~20-200 nm in diameter) that form when membranes are subjected to a point force. Tether dynamics are important to a myriad of biological processes including white blood cell adhesion and transport of intracellular material between neighboring cells. To understand the dynamics of tether formation more fully, we investigated the dependence of the force needed to create a tether on the rate of force change (loading rate). To conduct these experiments, a microfabricated magnetic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…An alternative and general explanation for the observed striking correlation of phase transition of the according lipid membrane and enzyme activity is provided by Kaufmann’s theory 41 , 43 as introduced above. This theory is perfectly in line with these and other experimental findings, which observe peaks correlating with the phase transition temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative and general explanation for the observed striking correlation of phase transition of the according lipid membrane and enzyme activity is provided by Kaufmann’s theory 41 , 43 as introduced above. This theory is perfectly in line with these and other experimental findings, which observe peaks correlating with the phase transition temperature.…”
Section: Resultsmentioning
confidence: 99%
“…If one susceptibility exhibits a peak, e.g., the lipid membrane undergoes a melting transition, due to the coupling, all susceptibilities will likely exhibit a peak. As the enzyme is part of the surface and shares a mutual thermodynamic potential, the enzyme activity is another susceptibility and is predicted to display a peak as well 32 , 43 , 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that this is also the case for originally water-soluble enzymes when bound to a lipid bilayer [21]. One theory to explain this effect is based on higher fluctuations that occur in the system within a phase transition [22], based on the original theory of Kaufmann [23]. These results make it seem plausible that artificial changes in the membrane environment, such as density modulations, affect the activity of AChE.…”
Section: Introductionmentioning
confidence: 83%
“…Kaufmann has developed a theory based on the second law of thermodynamics, according to which changes in catalytic activity represent changes in fluctuation strength of the reaction coordinate induced by the absorption of the substrate 9,10,44 . In another manuscript we indeed demonstrate that the catalytic rate of AChE directly follows the state (compressibility), and 11 hence the fluctuation strength of the interface in which the enzyme is embedded 30,39 .…”
Section: Figures 2a and B Display The Time-courses Of Simultaneous Dementioning
confidence: 99%